"Generalized unsafety" as fear inhibition to safety signals in adults with and without childhood trauma. Issue 4 (28th March 2022) - Huskey, Alisa; Taylor, Daniel J.; Friedman, Bruce H.
Abstract: The Generalized Unsafety Theory of Stress posits that low heart rate variability contributes to a perception of "generalized unsafety" (i.e., constantly perceiving oneself to be unsafe), independent of stressful events or stress‐related symptomatology. We tested this claim by examining if resting heart rate variability, trait worry, posttraumatic stress symptoms, trauma history, and age of onset predicted fear inhibition, a measure of generalized unsafety. A Pavlovian discriminant conditioning paradigm was used to assess fear inhibition level by comparing eyeblink startle potentiation to a threat cue (presented with air blast) with startle potentiation to a safety signal (never presented with air blast). Survey and laboratory responses were collected from 42 adults who were 20 years old on average, 86% Women, and 76% White. Heart rate variability did not independently predict variation in fear inhibition, as hypothesized. Rather, higher levels of posttraumatic stress symptoms and greater cumulative interpersonal trauma predicted lower fear inhibition. Individuals reporting childhood trauma had higher trait worry, which predicted more severe posttraumatic stress symptoms. These findings highlight the role of attenuated inhibitory learning in stress‐related symptomatology and developmentally disruptive trauma. Ability to distinguish threat from safety is a plausible biobehavioral mechanism by which adversity impacts development.